Peningkatan Motivasi Kader Kesehatan dalam Memberikan Pelayanan Prima Era Pandemi di Posyandu RW 05 Kecamatan Pademangan Timur Jakarta Utara - Pipin, Apriliana; Nur Rohmah, Ulfa; Ellynia, Ellynia; Juliani, Enni; Geltri Harahap, Sarah; Efkelin, Ria (PT.Mantaya Idea Batara, 2023)
Posyandu RW 05 Pademangan Timur is one of the posyandu that has routine work programs for the community, including during the pandemic. Cadres in psoyandu have an important role because they have the skills to develop posyandu. However, lack of motivation and the existence of pandemic constraints reduce the interest and motivation of cadres and do not understand the functions and duties of cadres in providing the best service, so this is a problem for partners in Posyandu RW 05, Pademangan Timur District, North Jakarta and as an approach to solving these problems it is important to hold counseling. This service is carried out at the Posyandu RW 05, Pademangan Timur District, North Jakarta. The method of service is counseling, discussion and question and answer, as well as assistance to cadres in implementing excellent service. The results of community service showed that there was an increase in the category of motivational knowledge of posyandu cadres and the implementation of excellent service by cadres.